Self-boundedness and self-hiddenness for implicit two-dimensional systems - Ntogramatzidis, Lorenzo (2015)
In this paper we introduce and develop the concepts of self-boundedness and self-hiddenness for implicit two-dimensional systems. The aim of this note is to show that when extending such concepts to a multidimensional setting, a richer structure arises than in the one-dimensional case.